An obstacle aware mobile sink path strategy in WSN - T. H. Feiroz Khan; D. Siva Kumar (Institute of Advanced Engineering and Science, 2019)
In Wireless Sensor Networks, Mobile Sink accomplishes considerable achievement on network lifetime improvement. In sensing environment, more chances to present the obstacle. But, in the mobile sink, how to identify the obstacle and make the obstacle aware path strategy is a challenging task. To overcome this problem, we propose an Obstacle Aware Mobile sink Path Strategy (OAMPS) that detects any obstacles which enter within the network lifetime and design a shortest mobile sink movement path avoiding detected obstacles. In this scheme, the mobile sink collects the sensing data from the super node then it sends the data to the base station. Here, static or moving obstacles are present when the mobile sink moves the path scheduling by spanning graph. This algorithm is introduced to discovering the obstacle avoiding shortest path. The source selects the route by the updated cuckoo search algorithm. The simulation results show that the OAMPS improved the throughput and minimized the delay in the network.